Optical Imaging and Gene Therapy with Neuroblastoma‐Targeting Polymeric Nanoparticles for Potential Theranostic Applications. Issue 9 (17th November 2015) - Lee, Jangwook; Jeong, Eun Ju; Lee, Yeon Kyung; Kim, Kwangmeyung; Kwon, Ick Chan; Lee, Kuen Yong
Abstract : Recently, targeted delivery systems based on functionalized polymeric nanoparticles have attracted a great deal of attention in cancer diagnosis and therapy. Specifically, as neuroblastoma occurs in infancy and childhood, targeted delivery may be critical to reduce the side effects that can occur with conventional approaches, as well as to achieve precise diagnosis and efficient therapy. Thus, biocompatible poly(d, l ‐lactide‐ co ‐glycolide) (PLG) nanoparticles containing an imaging probe and therapeutic gene are prepared, followed by modification with rabies virus glycoprotein (RVG) peptide for neuroblastoma‐targeting delivery. RVG peptide is a well‐known neuronal targeting ligand and is chemically conjugated to PLG nanoparticles without changing their size or shape. RVG‐modified nanoparticles are effective in specifically targeting neuroblastoma both in vitro and in vivo. RVG‐modified nanoparticles loaded with a fluorescent probe are useful to detect the tumor site in a neuroblastoma‐bearing mouse model, and those encapsulating a therapeutic gene cocktail (siMyc, siBcl‐2, and siVEGF) significantly suppressed tumor growth in the mouse model. This approach to designing and tailoring of polymeric nanoparticles for targeted delivery may be useful in the development of multimodality systems for theranostic approaches. Abstract : Ligand‐modified, gene‐loaded nanoparticles (NPs) are designed and prepared as a tumor‐targeting theranostic agent. Dye‐labeled NPs are modified with rabies virus glycoprotein peptide to enhance the receptor‐mediated uptake by neuroblastoma, and an siRNA cocktail (siMyc, siBcl‐2, and siVEGF) loaded in the NPs induces RNA interference and significantly suppresses tumor growth in a mouse model.